Text complexity - Fisher, Douglas (International Reading Association, 2012)
Selecting appropriate reading material for students is hard. For decades, teachers have known that quality instruction requires a careful matching of materials to students. The goal is to select materials that are neither too difficult nor too easy for students--a phenomenon sometimes called the Goldilocks Rule. To ensure that students learn to read increasingly complex texts, teachers have to understand what makes a text hard. The introduction of the Common Core State Standards has also placed a spotlight on text complexity. This book focuses on the quantitative and qualitative factors of text complexity as well as the ways in which readers can be matched with texts and tasks. It also examines how close readings of complex texts scaffold students understanding and allow them to develop the skills necessary to read like a detective